Tolai tabu as wealth and money: A shifting and unstable distinction. - Martin, Keir (History & Anthropology, 2018)
Distinctions between 'wealth' and 'money' such as the competing classifications of 'bridewealth' and 'brideprice' have a long pedigree in anthropology. Equally important has been the terminological struggle between 'shell-money' and 'shellwealth'. In this paper, I explore the ways in which a well-known example, Tolai tabu, circulates in the twenty-first century. I argue that whilst describing it as a form of wealth (in contrast to market-based idioms such as 'money' or 'price') continues to make sense, this distinction only comes into being from certain perspectives. In an era of rapidly emerging socio-economic inequality, the best starting point is not an assumed holistic opposition between Western commodity idioms and their non-Western Other. Ethnographic observation reveals how perspectives on tabu that stress its difference and similarity from money come in and out of being in different conversational contexts as an attempt to shape the limits of future relations and obligations.